Pengaruh Customer Experience terhadap Repurchase Intention Tamu di Favehotel Olo Padang - Feby Kasandi; Rahmi Fadilah (Asosiasi Peneliti Dan Pengajar Ilmu Sosial Indonesia, 2025)
This study aims to determine the influence of customer experience on guest repurchase intention at Favehotel Olo Padang. The background of this research is based on the importance of customer experience in shaping guests' desire to return to use Favehotel Olo Padang services. This study uses a quantitative approach with a causal associative descriptive method. Data collection was carried out through the distribution of questionnaires to 344 respondents who had or were staying at Favehotel Olo Padang. Data analysis was carried out by simple linear regression using the help of SPSS version 26. The results of the study show that customer experience has a positive and significant effect on repurchase intention. This is evidenced by a regression coefficient value of 0.864, and a significance value of 0.000 (< 0.05). An R-Square value of 0.755 indicates that 75.5% of the variation in repurchase intention can be explained by customer experience. Thus, it can be concluded that the better the experience felt by guests, the greater the likelihood of them returning to stay at Favehotel Olo Padang.